Chroicocephalus ridibundus Linnaeus 1766 - Bishop, K. David (Zenodo, 2023)
**BLACK-HEADED GULL Chroicocephalus ridibundus Status Vagrant. Scarce Palearctic migrant to New Guinea waters (Beehler & Pratt 2016) with just two records on Biak. 29‒30 March 1963: an immature in Biak harbour (King 1979); February 1991: eight at Biak wharf (Gibbs 1993). Published as part of Bishop, K. David, 2023, The avifauna of Biak Island, Papua, Indonesia with comments on status, conservation, natural history and taxonomy, pp. 3-62 in Bulletin of the British Ornithologists' Club 143 (1) on page 34, DOI:10.25226/bboc.v143i1.2023.a2, http://zenodo.org/record/11642130